ICTs in English language teaching: Positive teachers’ beliefs of ICT and their insufficient uses - Mitiku Garedew Tessema (ELT Forum: Journal of English Language Teaching, 2024)
Information and Communication Technologies (ICTs) are playing an important role in the teaching learning processes in the Ethiopian higher learning institutions. The purpose of this study was to investigate University English as Foreign Language (EFL) teachers’ beliefs and usage of ICTs in English language teaching. The study participants were English language teachers from a university in Ethiopia. Concurrent mixed methods research design and was employed in the study. Participants of the study were 29.  They were selected using total population sampling. The data were collected using a questionnaire and semi-structured interviews tools. The interview was conducted with teachers who were selected using purposive sampling. Then an interview was conducted with the selected teachers. The quantitative data were analyzed using descriptive statistics, tables and verbal descriptions. Next up, the qualitative data obtained from the interview were analyzed. The analysis was made based on the themes obtained from the research questions. Finally the discussion of the data was made by mixing both the quantitative and qualitative data. The findings of the study indicated that teachers' beliefs about the use of ICTs in English language teaching were positive; however, their practice was not to as their stated beliefs. Finally, the study recommended that English teachers should improve their utilization of the ICTs for ELT according to their stated beliefs. The university should also fix the technical problems of the language labs and provide English teachers with consecutive and practical training on how to use the available ICTs to improve the current ELT practices.